2018
DOI: 10.3324/haematol.2018.193128
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload impairs normal hematopoietic stem and progenitor cells through reactive oxygen species and shortens survival in myelodysplastic syndrome mice

Abstract: There is increasing clinical evidence to suggest a suppressive effect on hematopoiesis in myelodysplastic syndrome patients with iron overload. However, how iron overload influences hematopoiesis in myelodysplastic syndrome (MDS) remains unknown. Here, the RUNX1S291fs-transduced bone marrow mononuclear cells were yielded and transplanted into lethally irradiated recipient mice together with radioprotective bone marrow cells to generate MDS mice. Eight weeks post transplantation, the recipient mice received an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
3
41
0
1
Order By: Relevance
“…16 A previous study showed that iron overload could change the frequency and function of normal hematopoietic stem and progenitor cells, especially in erythroid cells. 17 Our findings are consistent with another study which found that iron overload may postpone hematopoietic recovery following BM transplantation, suggesting that iron overload may affect the hematopoietic microenvironment of BM. 18 Subsequently, observations revealed that colony formation, peripheral RBC counts and HGB concentration were reduced, while platelet counts were increased in response to iron overload after allo-HSCT.…”
Section: Allo-hsct In An Iron-overloaded Mice Negatively Impacts Susupporting
confidence: 93%
“…16 A previous study showed that iron overload could change the frequency and function of normal hematopoietic stem and progenitor cells, especially in erythroid cells. 17 Our findings are consistent with another study which found that iron overload may postpone hematopoietic recovery following BM transplantation, suggesting that iron overload may affect the hematopoietic microenvironment of BM. 18 Subsequently, observations revealed that colony formation, peripheral RBC counts and HGB concentration were reduced, while platelet counts were increased in response to iron overload after allo-HSCT.…”
Section: Allo-hsct In An Iron-overloaded Mice Negatively Impacts Susupporting
confidence: 93%
“…Previous studies have indicated that iron homeostasis is crucial for various kinds of stem cell. For example, iron overload can impact the self‐renewal and function of hematopoietic stem cells and progenitor cells [23,24], whereas iron deficiency impairs the pluripotency of hESCs/hiPSCs [15]. Besides, it has been reported that iron deficiency inhibited the expression of stemness markers and spherogenesis in cancer stem cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that iron homeostasis is critical for stem cells. For example, iron overload can affect the self‐renewal, frequency, and functioning of hematopoietic stem and progenitor cells . Thus far, little is known regarding the role of iron homeostasis in maintaining the biological property of PSCs.…”
Section: Introductionmentioning
confidence: 99%